The mediating effect of organizational innovation climate on enhancing the relationship between talent development practices and organizational performance - Majid, Zaid Hayder; Mohammed, Atheer Abdullah (Journal of Economics and Administrative Sciences, 2020)
The current, research, aims, to, verify, the relationship between talent development practices and organizational performance through a mediating role of creative organizational climate at the Institution of Industrial Development and Research- the Iraqi Industry Ministry. The descriptive and analytic approach was adopted as a research design. The research sample was represented by a number of managers and employees who work at the middle management level. The researchers used the questionnaire as the main method for collecting data to achieve the main research objective. It was distributed 162 questionnaires, of which 146 received; and then all of those were used on the final statistical analysis. The sample response-rate rate was 90%. The data, were, analyzed, using a number, of, statistical techniques such as weighted mean, standard deviation, simple determination coefficient, relative repetition, sample sufficiency test, confirmatory factor analysis, relative importance, Pearson coefficient, trend determination); all of these were within SPSS V.25 and AMOS V.25 software. The results indicate that all the research hypotheses were supported. Finally, the research reached a set of conclusions. The most important conclusion is that there is a direct impact between talent development practices and organizational performance. Moreover, this relationship can be indirectly improved when there is a high level of organizational innovation climate. This study is only limited to one organization (Industrial Development and Research) and one environment (manufacturing). Hence, the generalization of results to other sectors and organizations is difficult. Its intellectual boundaries were to verify the relationship between the influence of talent development practices on organizational performance and the mediation of the creative organizational climate). And its scientific implications was to verify the relationship between the influences of talent development practices on organizational performance and the mediation of the creative organizational climate. Because of the lack of studies in the Iraqi industrial organizations, especially in addition to the current trends that focus on how to develop our national products. Moving the variables under consideration towards the field reality, in order to form an applied knowledge base that represents one of the episodes of intellectual complementarity to the recommendations of previous studies and also adding a simple part of knowledge and thus is a starting point for many upcoming kinds of research and a solution to problems that may face industrial companies in the future through the recommendations that will be formulated. The research was drawn from a master thesis that was not discussed. This research represents a modest addition to the Iraqi academic stockpile in the field of management science and organizational behaviour studies and human resources on how talent development practices affect organizational performance through the central role of the creative organizational climate. Type of research - research paper.